2020
DOI: 10.21203/rs.3.rs-118298/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

New Intestinal Schistosomiasis Transmission Foci and Soil-transmitted Helminths Infection After Five Years of Preventive Chemotherapy and Associated Risk Factors Among School-aged Children in Two Districts in Southern Ethiopia

Abstract: Background: Preventive chemotherapy (PC), is the main elimination strategy against Soil-Tansmitted Helmenthiasis (STH) and Schistosomiasis (SCH) recommended by the world health organization (WHO), should be strengthened through identification of the remaining SCH transmission foci and evaluating its impact to get lesson. This study was aimed to assess the prevalence of STH/SCH infections, intensity of infections and associated factors among School Age Children (SAC) in two districts, previously not known to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 31 publications
(69 reference statements)
0
0
2
Order By: Relevance
“…Te higher prevalence of A. lumbricoides could be due to the fact that Ascaris eggs can withstand harsh environmental conditions more than the other species of STH and can easily sustain its transmission [51,52]. In contrast to the present study, several other studies have reported the predominance of hookworm over the other STH species [33,35,43,53,54]. Tis diference might be due to diferences in prevention measures used, climate variability, and other environmental factors.…”
Section: Discussioncontrasting
confidence: 92%
See 1 more Smart Citation
“…Te higher prevalence of A. lumbricoides could be due to the fact that Ascaris eggs can withstand harsh environmental conditions more than the other species of STH and can easily sustain its transmission [51,52]. In contrast to the present study, several other studies have reported the predominance of hookworm over the other STH species [33,35,43,53,54]. Tis diference might be due to diferences in prevention measures used, climate variability, and other environmental factors.…”
Section: Discussioncontrasting
confidence: 92%
“…In this study, most (93.7%) of the SAC reported having latrines on their premises. Similarly, the overall STH prevalence documented in this study is lower compared to studies conducted in diferent localities of Ethiopia such as Chencha district (39.4%), Sigmo district (41.7%), Ejaji town (38.2%), Gamo Gofa zone (33.3%), and northwest parts of Ethiopia (32.3%) [32][33][34][35][36], as well as studies conducted in other countries such as Rwanda (77.7%), Nigeria (59.2%), Indonesia (33.8% to 57.2%), and Malaysia (78.1%) [37][38][39][40][41].…”
Section: Discussioncontrasting
confidence: 66%